Three‐Component Gallium(III)‐Promoted Addition of Halide Anions and Acetylenes to Donor–Acceptor Cyclopropanes. (18th July 2018) - Novikov, Roman A.; Borisov, Denis D.; Tarasova, Anna V.; Tkachev, Yaroslav V.; Tomilov, Yury V.
Abstract: A new strategy for the three‐component addition of halide anions and acetylenes to donor–acceptor cyclopropanes (DACs) is presented. This reaction, which occurs with high E selectivity, is promoted by gallium(III) salts and based on the 1, 2‐zwitterionic reactivity of DACs. It opens up a new group of processes involving DACs. The reaction occurs readily with a broad range of substrates and is tolerant of various functional groups. This methodology makes it possible to assemble highly functionalized vinyl halides, which are very convenient building blocks in organic synthesis. A possible mechanism of this reaction and its stereochemical aspects are discussed in detail.